Lycopene Content and Antioxidant Properties of Pink Guava Industry by-Products - Kong, Kin Weng (2010)
Malaysia is one of the largest pink guava (Psidium guajava) puree exporters in the world. Daily production of the industry produces huge amount of the by-products. Thus, exploitation of these by-products as functional sources could reduce the disposal cost and problem. This study was aimed to investigate the lycopene content and antioxidant properties of these by-products and the lycopene-rich fractions produced from decanted by-product. The content of lycopene and lipophilic antioxidant capacity were compared among pink guava fruit by-products named accordingly to the processing points as refined by-product, sieved by-product and decanted by-product. Lycopene content was estimated using UV-VIS spectrophotometer and high performance liquid chromatography (HPLC) method. Atmospheric pressure chemical ionization liquid chromatography-mass spectrometry (APCI-LC-MS) was used to confirm the presence of lycopene. Lipophilic antioxidant capacity was assessed using lycopene equivalent antioxidant capacity (LEAC) and β-carotene bleaching assays. Lycopene content and antioxidant capacity were in the order of fruits > decanted by-product > sieved by product > refined by-product. Decanted by-product was found to be the highest lycopene content and antioxidant capacity among the by-products. Heat treatment through steam blanching was applied to find the best conditions for lycopene content in the studied by-products. Steam blanching at 60°C for 20-60 min significantly (p < 0.05) increased lycopene content in decanted by-product to about 13% from the freeze-dried control. To further optimise drying conditions for lycopene and lipophilic antioxidant capacity in the studied by-products, decanted by-product was dried with different temperatures (50-80ºC) and drying times (4-6 h) using an oven dryer based on the response surface methodology (RSM). Response surface plots showed increase in temperature and time significantly (p < 0.05) reduced the response variables. The optimum oven conditions for drying of decanted by-product with minimum lycopene degradation were at 43.8ºC for 6.4 h. Besides, the effects of solvent and supercritical carbon dioxide (SC-CO2) extractions on antioxidant capacity and cytotoxicity in lycopene-rich fractions (hydrophobic fractions) were also determined using LEAC, β-carotene bleaching and MTT (3-(4, 5-dimethylthiazole-2yl)-2, 5-diphenyl tetrazolium bromide) assays. Extraction with SC-CO2 exhibited higher lycopene content than the solvent extraction. No cytotoxicity was found on human normal liver cell lines supplemented with both extracts at concentrations ranged from 6.25-200 μg/ml. Protective effects of lycopene-rich fraction against H2O2-induced cells damage were observed at concentrations of 2.32 μM of lycopene (25 μg/ml) and 5.09 μM of lycopene (200 μg/ml) for solvent and SC-CO2 extracts, respectively. However, treatments with 200 μg solvent extract/ml containing 18.65 μM lycopene and 10 μM lycopene standard (Sigma Chemical Co.,USA) were found to provide the protective effect towards oxidative DNA damage evaluated by Alkaline Comet assay. Lycopene-rich fraction from pink guava by-products have the potential to be used as functional food ingredients in preventing the promotion of oxidative stress.